Are There Environmental Benefits from Driving Electric Vehicles? The Importance of Local Factors - Holland, Stephen P.; Mansur, Erin T.; Muller, Nicholas Z.; Yates, Andrew J. (The American economic review, 2016)
We combine a theoretical discrete-choice model of vehicle purchases, an econometric analysis of electricity emissions, and the AP2 air pollution model to estimate the geographic variation in the environmental benefits from driving electric vehicles. The second-best electric vehicle purchase subsidy ranges from $2,785 in California to —$4,964 in North Dakota, with a mean of —$1,095. Ninety percent of local environmental externalities from driving electric vehicles in one state are exported to others, implying they may be subsidized locally, even when the environmental benefits are negative overall. Geographically differentiated subsidies can reduce deadweight loss, but only modestly.